Experimental realization of state transfer by quantum walks with two coins. (24th December 2019) - Shang, Yun; Li, Meng
Abstract: Quantum state transfer is an important task for scalable quantum complex networks. By selecting quantum walks with two coins as the basic model and two coin spaces as the communication carriers, we successfully implement some perfect state transfer tasks on various graphs (Shang et al 2019 Europhys. Lett. 124 60009). Here, we provide the first experimental realization of this scheme by IBM Quantum Experience platform. Especially, we demonstrate the transfer of Bell state, GHZ state and W state on complete graph through this quantum apparatus. Furthermore, we notice that our protocols have high fidelity by performing quantum state tomography.